Hypoxia-Inducible Factor 1 is Essential for Spontaneous Recovery from Traumatic Brain Injury and is a Key Mediator of Heat Acclimation Induced Neuroprotection. Issue 4 (April 2013) - Umschweif, Gali; Alexandrovich, Alexander G; Trembovler, Victoria; Horowitz, Michal; Shohami, Esther
Heat acclimation (HA), a well-established preconditioning model, confers neuroprotection in rodent models of traumatic brain injury (TBI). It increases neuroprotective factors, among them is hypoxia-inducible factor 1α (HIF-1α), which is important in the response to postinjury ischemia. However, little is known about the role of HIF-1α in TBI and its contribution to the establishment of the HA protecting phenotype. Therefore, we aimed to explore HIF-1α role in TBI defense mechanisms as well as in HA-induced neuroprotection. Acriflavine was used to inhibit HIF-1 in injured normothermic (NT) or HA mice. After TBI, we evaluated motor function recovery, lesion volume, edema formation, and body temperature as well as HIF-1 downstream transcription targets, such as glucose transporter 1 (GLUT1), vascular endothelial growth factor, and aquaporin 4. We found that HIF-1 inhibition resulted in deterioration of motor function, increased lesion volume, hypothermia, and reduced edema formation. All these parameters were significantly different in the HA mice. Western blot analysis and enzyme-linked immunosorbent assay showed reduced levels of all HIF-1 downstream targets in HA mice, however, only GLUT1 was downregulated in NT mice. We conclude that HIF-1 is a key mediator in both spontaneous recovery and HA-induced neuroprotection after TBI.